Analysis of the Effect of Business Strategy, Debt Policy, and the Age of the Company on Tax Avoidance (Lembaga Penerbitan Unversitas Esa Unggul, 2022)
This research aims to investigate whether business strategy, debt policy, and the age of the company influence tax avoidance. The sample of this research is a food and beverage sector company listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique uses the purposive sampling method with a total sample of 81 companies. The data analysis technique uses multiple linear regression analysis. The results of this research show that the business strategy and the age of the company variable do not affect tax avoidance, while the debt policy variable has a significant effect on tax avoidance. The implications of this research provide empirical evidence regarding the influence of business strategy, debt policy, and the age of the company on tax avoidance. The limitation of this research is that the sample used is limited to only food and beverage sector companies listed on the IDX in the 2018-2021 period. Therefore, future research can increase the number of samples and years of research.